MOBILE-BASED CAR BOOKING SERVICE APPLICATION AT SRIWIJAYA BERLIAN CAR REPAIR SHOP - Fakhri Lambardo; Wawan Wawan (Informatika, Universitas Jenderal Soedirman, 2022)
Current technological developments are needed to help companies face competition, especially in conveying information to many people. Sriwijaya Berlian Car Repair Shop does not yet have a flow in booking service. Therefore, an application is needed to help admins in booking services and make it easier for customers to make reservations. The method in making this application starts from gathering requirements, making prototypes and designing, implementing in the form of applications, and conducting testing. After passing the development stage, a mobile-based application and website for booking services were produced at the Sriwijaya Berlian Car Repair Shop. Based on the results of the blackbox test, it was found that the application was in accordance with what was expected by the application developer, while based on the results of the user acceptance test, the user's average perception was 88.88% with the indicator category